Shear Bond Strength of Composite Repair System to Bilayered Zirconia Using Different Surface Treatments (In Vitro Study) - Baiomy, Ahmed Atef; Younis, Jihan Farouk; Khalil, Ahmed Hassanen (Brazilian Dental Science, 2020)
Objective: the study is aimed to evaluate the effect of different surface treatment methods on shear bond strength between composite repair system and both of zirconia core and veneering porcelain and analyze the mode of failure between composite repair and ceramic surface. Material and methods: 40 Ceramic discs were fabricated with diameter of 7mm and 3mm thickness and divided according to material into two groups, Zirconia core discs (n = 20) and veneering porcelain discs (n = 20). Specimens were thermocycled and then each group was subdivided according to surface treatment method into 4 equal sub groups (n = 5) ,control subgroup I air abrasion, subgroup II Cojet, subgroup III laser, subgroup IV combination of air abrasion and laser surface treatment. Composite blocks were built up and polymerized on the surface of the specimens and shear bond strength of composite to each specimen was tested using a universal testing machine and mode of failure was evaluated using stereomicroscope. Results: Regardless of ceramic type; there was a statistically significant difference between surface treatments. Cojet recorded the highest mean shear bond strength. Laser showed the highest prevalence of adhesive failure. Porcelain + Cojet showed the highest prevalence of cohesive failure. Conclusion: Cojet surface treatment provided superior shear bond strength regardless of the ceramic type whether zirconia or porcelain. Porcelain provided superior shear bond strength values in comparison to zirconia regardless of the surface treatment method tested. Porcelain showed higher percentage of cohesive failure that while the mode of failure in zirconia was most commonly adhesive. KEYWORDS Laser; Porcelain repair; Zirconia repair.